ANALISIS VISUAL STORYTELLING PADA POSTER FILM “BUMI MANUSIA” - Satriadi, Satriadi; Adinda, Shafa (JURNAL PAKARENA, 2023)
Film posters are important aspects of visual communication since they serve not only as a commercial tool but also as a medium full of significance, particularly in the film "Bumi Manusia" by Falcon Pictures, which accurately depicts the Dutch colonial era through rigorous study. This study uses a qualitative technique to evaluate the poster for the film "Bumi Manusia." The data collection method employs two basic sources: primary data and secondary data. Primary data is gathered through direct observation of the poster, allowing researchers to examine visual components such as color, imagery, and text. Meanwhile, secondary information is derived from external sources such as journals, papers, and books, and it serves to supplement or reinforce the conclusions of direct observations. The research technique consists of four steps of design review: work description, formal analysis, interpretation, and evaluation. Thus, the film poster "Bumi Manusia" captures the film's story and atmosphere in detail using visual art. This poster illustrates the cultural and political clash at the center of the story using detailed images of the main protagonists. Color, font, photography, and good composition are used in these posters to strengthen the formal narrative. The poster's interpretations underlined the complexities of cultural and political struggle, while the study determined that the poster accurately reflected the delicate relationship between Dutch indigenous and colonial peoples. This poster highlights the complexities of the cultural and social life of the time, which is relevant to the film's theme.